Dinamika Peran Perempuan dalam Pendidikan Tinggi Menurut Perspektif Islam : Studi Kasus Analisis Pandangan Masyarakat Dukuh Binangun - Aeni, Delliana Fitri (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2025)
The existence of local culture and society's mindset towards women in higher education is the main point. Some parents prioritize boys' education and ignore girls' education, so it is not surprising that a girl's identity development is retarded. As according to Islam stated in Q.S. al-Mujadilah: 11 which means: "Allah raises the status of those who believe and those who seek knowledge to varying degrees." The research method used is a qualitative descriptive approach with data collection techniques obtained through interviews and observations in Kwasen Dukuh Binangun Kesesi Village, Pekalongan. The research results illustrate that village communities are still influenced by local culture which believes that women's education is not important and is often ignored because they prioritize men's education. This has an impact on barriers to women's development and mentality. However, there is also an open mindset in society. Where they support the importance of higher education for women as a tool to improve the quality of life and create social change. In this context, the dynamics of women's roles in higher education illustrate their struggle to overcome cultural and economic barriers. The government also provides various scholarships as an effort to overcome economic obstacles. Therefore, increasing public awareness of women's higher education is expected to overcome these obstacles and provide greater opportunities for women to obtain higher education.